Hubungan Kebiasaan Konsumsi Makanan Sumber Seng dan Zat Besi serta Kejadian Diare dengan Kejadian Stunting pada Balita Usia 1-3 Tahun di Wilayah Kerja Puskesmas Sungai Jering Kabupaten Merangin - Dwi Sriwinarsih; Djayusmantoko Djayusmantoko; Merita Merita (Universitas Baiturrahim, 2020)
Stunting is a condition of failure to achieve physical development is measured based on height according to age. The purpose of this study was to determine the relationship of food habit consumtion of zinc and iron sources and as well as diarrhea incidence with stunting on the toddler aged 1-3 years I work of community health center of Sungai Jering, Merangin 2019 years.The study was used a Cross Sectional desigh study. This study was concucted in work area Puskesmas Sungai Jering on July 2019. The population of this study was 221 toddlers, total of sampels was 67 toddlers with the technique Proporsional Random Sampling. The data was taken using Food Frequency Questionnarie (FFQ) and interview. The data was analyzed using univariate and bivariate (Chi-Square).The result showed that 55% of toddlers not of stunting, 52,5% of toddlers have habit comsumtion of Zn category was rarely, of 53,8% have habit comsumtion of Fe category was rarely, and 72,5% not diarrhea. There is significant relationship between habit comsumtion of Zn and incidence of stunting(p = 1,000), there is a significant relationship between habit comsumtion of Fe and incidence of stunting (p = 0,529) and there is a significant relationship between the the incidence of diarrhea and the incidence of stunting (p =0,000 ) among toddlers.I can be concluded that there is a significant relationship between the inciedence of diarehea with the incidence of stunting the for the mother of a toddler can keep food hygiene to reduce the occurrence of stunting . Therefore, it is advisable in mother and toddlers so can increase the nutritional knowledge about the way of eathing that is good for toddlers and maintain the cleaniness of the food so that it can improve the nutritional status of children.